Lithospheric Structure Across the Alaskan Cordillera From the Joint Inversion of Surface Waves and Receiver Functions. Issue 10 (9th October 2018) - Ward, Kevin M.; Lin, Fan‐Chi
Abstract: The final deployment stage of the USArray Transportable Array is nearly complete with several years of high‐quality broadband seismic data across the Northern American Cordillera already publicly available. This section of the Cordillera represents a rich history of tectonic deformation and accretion events as well numerous active tectonic processes. Many of these active tectonic processes such as uplift mechanisms or magmatic systems have been interpreted from structures imaged in regional or limited 2‐D studies. To investigate the fully 3‐D nature of the crust and uppermost mantle (<70 km), we present the results of a joint receiver function, surface wave inversion for the shear wave velocity structure across the Alaskan Cordillera. Integration of our new isotropic velocity model with existing data sets, including seismicity, gravity anomalies, and other seismic imagining methods, indicates that our velocity model is consistent with previous studies while providing unprecedented additional detail. A prominent feature in our model is a low‐velocity mantle wedge. We suggest this low‐velocity mantle wedge results from subducting slab lithosphere. The tectonic significance of this interpretation is that the velocity anomaly extends further to the east than slab seismicity does, suggesting that the downgoing slab extends further to the east, albeit aseismicly. This interpretation provides a simple explanation for the location of the active Wrangell volcanoes. We expect that our velocity model will be integrated with other mantle tomography models to further refine our understanding of this complex tectonic setting. Key Points: We present a new 3‐D shear‐wave velocity model for the crust and uppermost mantle beneath the Alaskan Cordillera We observe a low-velocity mantle wedge that extends further east than located slab seismicity Our results are consistent with numerous lithospheric structures seen in previous geophysical studies